Teacher Commands and Prohibitions in Classroom Interaction: An Ethnopragmatic Analysis of Liberal and Conservative Indonesian Language Teachers - Agus Purnomo Ahmad Putikadyanto; Asep Setiadi (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study examines directive speech acts in the form of commands and prohibitions used by Indonesian language teachers with liberal and conservative ideological orientations in classroom learning interactions. The study employs a qualitative research design with an ethnographic approach. The data were obtained from the utterances of seven liberal- and conservative-oriented teachers across four educational institutions at different levels (junior and senior high schools) in Malang City. The selection of teachers from different educational levels was intended to represent variations in pedagogical practices based on students’ developmental stages, while Malang City was chosen due to its diversity of educational institutions and academic cultures that allow for the emergence of varied ideological orientations and directive speech strategies, particularly commands and prohibitions. Data were collected through classroom observations, in-depth interviews, and documentation. The findings reveal clear differences in the use of directive speech acts of commands and prohibitions between liberal and conservative teachers. Liberal-oriented teachers tend to employ indirect directive strategies that emphasize politeness, dialogue, and learner autonomy, thereby creating a more egalitarian and participatory classroom atmosphere. In contrast, conservative-oriented teachers more frequently use direct and explicit directive speech to maintain order, discipline, and clarity of instruction. Both groups demonstrate communicative flexibility by adjusting directive strategies to situational demands, indicating that the use of commands and prohibitions is dynamic and context-dependent. These findings affirm that directive speech acts of commands and prohibitions reflect teachers’ cultural values and ideological orientations and have important implications for the success of Indonesian language learning in the classroom.